Drinking Water Disinfection By-products, Genetic Polymorphisms, and Birth Outcomes in a European Mother–Child Cohort Study. Issue 6 (November 2016) - Kogevinas, Manolis; Bustamante, Mariona; Gracia-Lavedán, Esther; Ballester, Ferran; Cordier, Sylvaine; Costet, Nathalie; Espinosa, Ana; Grazuleviciene, Regina; Danileviciute, Asta; Ibarluzea, Jesus; Karadanelli, Maria; Krasner, Stuart; et al.
Abstract : Background: We examined the association between exposure during pregnancy to trihalomethanes, the most common water disinfection by-products, and birth outcomes in a European cohort study (Health Impacts of Long-Term Exposure to Disinfection By-Products in Drinking Water). We took into account exposure through different water uses, measures of water toxicity, and genetic susceptibility. Methods: We enrolled 14, 005 mothers (2002–2010) and their children from France, Greece, Lithuania, Spain, and the UK. Information on lifestyle- and water-related activities was recorded. We ascertained residential concentrations of trihalomethanes through regulatory records and ad hoc sampling campaigns and estimated route-specific trihalomethane uptake by trimester and for whole pregnancy. We examined single nucleotide polymorphisms and copy number variants in disinfection by-product metabolizing genes in nested case–control studies. Results: Average levels of trihalomethanes ranged from around 10 μg/L to above the regulatory limits in the EU of 100 μg/L between centers. There was no association between birth weight and total trihalomethane exposure during pregnancy ( β = 2.2 g in birth weight per 10 μg/L of trihalomethane, 95% confidence interval = 3.3, 7.6). Birth weight was not associated with exposure through different routes or with specific trihalomethane species. Exposure to trihalomethanes was not associated with low birth weight (odds ratio [OR] per 10 μg/L = 1.02, 95% confidence interval = 0.95, 1.10), small-for-gestational age (OR = 0.99, 0.94, 1.03) and preterm births (OR = 0.98, 0.9, 1.05). We found no gene–environment interactions for mother or child polymorphisms in relation to preterm birth or small-for-gestational age. Conclusions: In this large European study, we found no association between birth outcomes and trihalomethane exposures during pregnancy in the total population or in potentially genetically susceptible subgroups. (See video abstract athttp://links.lww.com/EDE/B104 .) Abstract : Supplemental Digital Content is available in the text.